Professional competences of environmental engineer and the knowledge of physics required for their formation - Chikova, Tamara S.; Golovatyi, Sergey E.; Maskevich, Sergey A. (Journal of the Belarusian State University. Ecology, 2022)
The role of environmental risks, the solution of which determines the preservation and progress of civilization, is analyzed. The article substantiates the growing importance of the ecologist profession in the modern world and the need to expand the range of environmental specialties. The characteristic of the professional competencies of an environmental engineer is given. The role of physics in the formation of knowledge and skills necessary for the successful implementation of professional competencies of an ecologist is noted. The basic laws and regulations of physics are considered, the knowledge of which provides effective training of environmental specialists in the field of environmental protection. It is shown that taking into account the importance of interdisciplinary knowledge in understanding the relationship between natural and man-made processes, as well as the role of the anthropogenic factor in global environmental problems, the modern traditional structure of physical education in the system of professional training of an environmental engineer in a higher educational institution requires improvement